Impact of Vocational Training Programme on Income and Employment Generation for Rural Youth in Dewas District of Madhya Pradesh - Gupta, Nishith; Patel, Neerja; Bhargav, K.S.; Singh, Moni; Dixit, A.K. (Indian Journal of Extension Education, 2018)
Various efforts for agriculture and rural development have been made by the government to encourage the farmers to adopt new agricultural technologies and efficient practices to change their situations for economic prosperity and livelihood security. In this regard Krishi Vigyan Kendra, Dewas (MP) conducted vocational trainings for rural youths on “Nursery Management of vegetables” and “Vegetative propagation techniques in fruit plants” from 2007-2012, 2014 and 2016 with the objective to give rural youths self employment. the results revealed that majority (53.33%) of respondents had low income, while 26.67 percent and 20.00 percent were in medium and high income categories, respectively. Higher percentage (50.00%) of the respondents were of medium income category, while 36.67 per cent and 13.33 per cent were of low and high income categories, respectively.
Keywords: Agricultural technologies; employment; income; vocational trainings